2019
DOI: 10.1091/mbc.e18-10-0626
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stresses induce karyotypic instability in colorectal cancer cells

Abstract: Understanding how cells acquire genetic mutations is a fundamental biological question with implications for many different areas of biomedical research, ranging from tumor evolution to drug resistance. While karyotypic heterogeneity is a hallmark of cancer cells, few mutations causing chromosome instability have been identified in cancer genomes, suggesting a nongenetic origin of this phenomenon. We found that in vitro exposure of karyotypically stable human colorectal cancer cell lines to environmental stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…However, conditions in the extracellular environment can increase the frequency of aberrant mitoses. Various environmental stresses can induce gene mutations or CIN [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. The specific effects of these stresses are modulated by the nature, magnitude, and duration of the stress.…”
Section: Environmental Causes Of Karyotype Changementioning
confidence: 99%
“…However, conditions in the extracellular environment can increase the frequency of aberrant mitoses. Various environmental stresses can induce gene mutations or CIN [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. The specific effects of these stresses are modulated by the nature, magnitude, and duration of the stress.…”
Section: Environmental Causes Of Karyotype Changementioning
confidence: 99%
“…To study the consequence of WGD in human cells, we previously developed geneticallymatched systems of human colon cancer cell lines before and after WGD (Kuznetsova et al 2015;Tan et al 2019;Bloomfield et al 2021).…”
Section: Isogenic Human Cancer Cell Lines Reveal a Causal Relationship Between Wgd And Aneuploidy Landscapesmentioning
confidence: 99%
“…We identified distinct aneuploidy recurrence patterns and chromosome-arm genetic interactions in WGD-vs. WGD+ tumors, then validated these results in human cancer cell lines. Furthermore, we studied the relationship between WGD and aneuploidy using genetically-matched systems of human colon cancer cell lines before and after WGD (Kuznetsova et al 2015;Tan et al 2019;Bloomfield et al 2021). Our findings suggest that WGD is a major determinant of aneuploidy evolution in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies revealed that human cells in mitosis exposed to heat shock can result in polyploid or tetraploid cells by directly entering interphase without completing division due to the disassembled spindle and destroyed contractile ring [29,30,31]. Tan et al [32] found that that heat shock causes polyploidization of human colon carcinoma cell lines by mitotic exit without chromosome segregation. Furthermore, cytokinesis failure can generate tetraploidy that can undergo multipolar divisions and promote tumorigenesis in p53-null cancer cells [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cell fusion is another mechanism for cancer cells to exhibit a higher degree of aneuploidy [35,36]. The above polyploid cancer cells and their aneuploid daughter cells caused by heat treatment may induce tumor heterogeneity and further drug resistance [32,37,38]. Since heat stress can lead to alterations in centrosomes and different abnormal biological routes, such as mitotic slippage, cytokinesis failure, or cell fusion, it can be directly observed and responsible for the formation of polyploid cells after heat stress treatment.…”
Section: Introductionmentioning
confidence: 99%